Sustainability assessment and prioritisation of e-waste management options in Brazil - Souza, Ricardo Gabbay de; Namorado Climaco, Joao C.; Sant'Anna, Annibal Parracho; Rocha, Tiago Barreto; Bastos do Valle, Rogerio de Aragao; Goncalves Quelhas, Osvaldo Luiz (Elsevier B.V., 2016)
Brazil has an increasing rate of e-waste generation, but there are currently few adequate management systems in operation, with the largest share of Waste Electrical and Electronic Equipment (WEEE) going to landfill sites or entering informal chains. The National Solid Waste Policy (2010) enforces the implementation of reverse logistics systems under the shared responsibility of consumers, companies and governments. The objective of this paper is to assess sustainability and prioritise system alternatives for potential implementation in the metropolitan region of Rio de Janeiro. Sustainability criteria and decision alternatives were defined by elicitation of stakeholders. The adopted multicriteria approach combines Life Cycle Assessment with qualitative evaluations by a small sample of regional experts with knowledge of the problem. The recommended system consists of a hybrid WEEE collection scheme with delivery points at shops, metro stations and neighbourhood centres; a pre-treatment phase with the involvement of private companies, cooperatives and social enterprises; and full recycling of all components in the country. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Waste electric and electronic equipment; Reverse logistics; Multicriteria decision analysis; Composition of probabilistic preferences; Life cycle assessment; Sustainability assessment